2008
DOI: 10.1007/s12098-008-0122-6
|View full text |Cite
|
Sign up to set email alerts
|

Peters plus syndrome

Abstract: A 10-year-old boy, issue of unrelated parents presented with visual impairment, short stature and mental retardation. The presence of a Peters' anomaly, mental retardation, disproportionate short stature, skeletal abnormalities and distinctive facial features (broad forehead, telecanthus, cupid bow shaped upper lip) established the diagnosis of Peters' plus syndrome. Analysis of his genomic DNA revealed a homozygous deletion in the beta1,3-galactosyltransferase-like gene (B3GALTL), a recently identified gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…Consecutive dislocation of the hypoplastic cerebellum had already been recognized in prenatal ultrasound. In few PPS cases from the literature, spina bifida occulta L5-S1 30 and also sacral dimples were reported. 3,19,21 Association of the latter with an underlying vertebral schisis is controversially discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Consecutive dislocation of the hypoplastic cerebellum had already been recognized in prenatal ultrasound. In few PPS cases from the literature, spina bifida occulta L5-S1 30 and also sacral dimples were reported. 3,19,21 Association of the latter with an underlying vertebral schisis is controversially discussed.…”
Section: Discussionmentioning
confidence: 99%
“…The role of B3GALTL in PPS was recently identified with splicing mutations/deletions identified in 20 of 20 patients [18], including a recurrent c.660+1G>A mutation. Subsequent screens revealed mutations/deletions in nine additional patients with typical PPS [98-101*,102*]; splicing mutations are the most commonly seen. Review of these previous reports suggests that the presence of ASD, short stature, brachydactyly, and characteristic facial features is predictive of B3GALTL mutations while no mutations in B3GALTL were identified in eight patients with atypical PPS (some but not all of these typical features) (Table 3) [99, 101*, 104*].…”
Section: Autosomal Recessive Anterior Segment Dysgenesesmentioning
confidence: 99%
“…3 Recently a mutation in the beta 1,3-glucosyltransferase gene, an enzyme that plays a role in protein glycosylation, was described in patients with typical Peters plus syndrome. 4,9 Patients with an atypical phenotype of Peters anomaly did not show this mutation. 9 We therefore chose not to pursue testing for this genetic mutation since a different mutation was detected, as discussed below.…”
Section: Discussionmentioning
confidence: 92%
“…It was traditionally thought that bilateral cases, not unilateral cases, were linked with genetic conditions and extraocular findings. 3,4 Some researchers, however, have found that this may not necessarily be true. Traboulsi and Maumenee 5 reviewed 29 patients with Peters anomaly and found that 45% of patients with unilateral involvement had systemic associations (Peters plus syndrome) or developmental delay versus 67% of patients with bilateral disease.…”
Section: Discussionmentioning
confidence: 99%